PANDANGAN WISATAWAN DAN TATA KELOLA OBJEK WISATA TELAGA AJAIB TARUSAN KAMANG DI KABUPATEN AGAM - Rahman Hidayu; Erwin Erwin; Afrizal Afrizal (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
Telaga Ajaib Tarusan Kamang is located in Agam Regency. In the past several years there has been issue on decreasing visitor number who interested to visit the tourism object. The main cause of the issue was improper tourisms management that lead to tourist perspective towards the object.The objective of this study is to seek visitors view toward the object and to define how the governance of Telaga Ajaib Tarusan Kamang works. The study utilize qualitative descriptive method that collect the data obtained from study outcome in regards of administer of the object and how tourists view tourism objects. Data collection was obtained by observation, depth interview, and documentation. Tourism governance is a form of connection between tourism person with resources, consumers, government and the parties that share common interest. In tourism governance, there are 4 basic management functions shall applied, consist of POAC (Planning, Organizing, Actuating and Controlling). Furthermore, there are 4 aspects of tourism that must be managed properly,includes attractions, facilities, infrastructure and transportation. Tourists' views on the Telaga Ajaib Tarusan Kamang Tourism did not show quite satisfaction. It is very understandable since the 4 keys for a successful tourisms such as attractions, facilities, infrastructures and transportation have not been able to meet the needs of tourists. This is most likely caused by the governance of Telaga Ajaib Tarusan Kamang Tourism is not properly managed. Taken from the principle of management, there are indeed several planning set by local management along with the government, but in terms of organizing, actuating and controlling it has not properly executed . However the suggestion to the administor to be more aggressive in socializing in regards of sustainability tourisms environmental to the locals and provide more facility that may result in visitors satisfaction.